Effect of the stress ratio on the fatigue behavior of Zr55Al10Ni5Cu30 bulk metallic glass. Part II — Reconfirmations and new findings on the crack propagation mechanism. (February 2018) - Guennec, Benjamin; Nobori, Takuya; Kuwahara, Hirotaka; Ueno, Akira
Abstract: The assessment of the reliability of Bulk Metallic Glasses (BMGs) as structural materials needs further investigations, particularly dealing with the impact of the loading condition on the fatigue behavior. Stress ratio R is one of these important parameters associated with the fatigue loading. The present work investigates the high-cycle fatigue properties of Zr55 Al10 Ni5 Cu30 BMG at three distinct stress ratios from 0.1 to 0.7. Even though Part I of the present study has been mainly focused on the fatigue resistance considerations, a peculiar feature was found on the fracture surface at stress ratio of R = 0.7. Thus, this second part is investigating the fatigue crack propagation behavior of Zr55 Al10 Ni5 Cu30 BMG. Experimental results highlight a crack propagation behavior at R = 0.1 and 0.4 similar to the results reported in the research field. On the other hand, observations of fracture surface and tensile surface of specimens failed at high stress ratio of R = 0.7 underline a peculiar crack propagation behavior. Highlights: Effect of stress ratio R was studied in the range from 0.1 to 0.7. Crack propagation was recorded by a newly developed in-situ system. Crack propagation behavior at R = 0.1 and 0.4 is comparable to reported results. Some irregularities on fracture and tensile surfaces were detected at R = 0.7. Authors are proposing a crack propagation model to explain these irregularities.